2014
DOI: 10.1111/clr.12489
|View full text |Cite
|
Sign up to set email alerts
|

Papilla dimension and soft tissue level after early vs. delayed placement of single‐tooth implants: 10‐year results from a randomized controlled clinical trial

Abstract: Early placement of single-tooth implants after tooth extraction performed equally to delayed placement in regard to the esthetic outcome of the soft tissues after 10 years in function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 35 publications
5
66
0
Order By: Relevance
“…It is also important to follow implant placement protocols as they continue to develop. Promising clinical outcomes have been reported for a modification of the early placement protocol where implants were placed 10 days after extraction . Schropp and colleagues have shown comparable clinical outcomes between this protocol and the delayed implant placement protocol after 5‐years and 10‐year follow‐up periods …”
Section: Discussionmentioning
confidence: 99%
“…It is also important to follow implant placement protocols as they continue to develop. Promising clinical outcomes have been reported for a modification of the early placement protocol where implants were placed 10 days after extraction . Schropp and colleagues have shown comparable clinical outcomes between this protocol and the delayed implant placement protocol after 5‐years and 10‐year follow‐up periods …”
Section: Discussionmentioning
confidence: 99%
“…This placement technique has been shown to achieve acceptable long term clinical as well as esthetic outcomes by maintaining the width of buccal bone around implants in the anterior maxilla . Long‐term soft tissue changes around implants inserted using an early placement protocol have also been shown to be comparable to conventional implant (Type 3 and 4) placement . Although promising results have been shown with early placed implants, evidence on the esthetic outcomes of this technique is still limited, especially in comparison to other placement protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Araú jo et al elucidated in an animal study using a dog that the placement of an implant in the fresh extraction site does not prevent remodeling in the socket wall at 3 months after tooth extraction [38]. A number of clinical reports on immediate placement have been published since then [39][40][41], and it was demonstrated that bone resorption cannot be prevented completely by immediate placement. The results of a systematic review regarding alterations of the bone dimensions following immediate implant placement into an extraction socket by Lee et al showed that the median amount of buccal bone resorption at 4-12 months after immediate placement was 1.07 mm horizontally and 0.78 mm vertically [42].…”
Section: Immediate or Early Implant Placementmentioning
confidence: 99%